2014
DOI: 10.1155/2014/567124
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Driver Injury Severity at Intersection: An Ordered Probit Analysis

Abstract: It is well known that intersections are the most hazardous locations; however, only little is known about driver injury severity in intersection crashes. Hence, the main goal of this study was to further examine the different factors contributing to driver injury severity involved in fatal crashes at intersections. Data used for the present analysis was from the US DOT-Fatality Analysis Reporting System (FARS) crash database from the year 2011. An ordered probit model was employed to fit the fatal crash data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Since the dependent variable,Zi, is unobserved, standard regression techniques cannot be applied to compute Eq (1). Therefore, one can reasonably assume that a high risk of injury, denoted by Zi is related to a high level of observed injury, denoted by Yi [25][26][27]. This relationship can be translated as follows…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since the dependent variable,Zi, is unobserved, standard regression techniques cannot be applied to compute Eq (1). Therefore, one can reasonably assume that a high risk of injury, denoted by Zi is related to a high level of observed injury, denoted by Yi [25][26][27]. This relationship can be translated as follows…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…All of these variables, with the exception of the variable age of the orthopedic crash victims are binary with means between 0 and 1. The variable age (continuous variable) has been scaled (dividing by 100) to have mean with the same scale as those of the binary, since Ordered Probit (OP) models may not converge if the variables have not similar scales (25)(26)(27).…”
Section: Road Traffic Crash Injury Severity Estimates Using An Ordered Probit Modelmentioning
confidence: 99%
“…Zhang et al (2015) [11] and Makarova et al (2020) [24] also add "crash characteristics" as the fifth group, which describes a situational setting, such as the manner of collision (e.g., rear-end, head on, hitting an object, dropping an item).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The limitations of the reviewed studies are identified, and this study contribution is discussed. The studies [35][36][37][38][39] had a common limitation as they did not consider pavement friction in the analyses.…”
Section: Literature Reviewmentioning
confidence: 99%